High freezing rate improves flavor fidelity effect of hand grab mutton after short-term frozen storage - Bi, Yong-Zhao; Luo, Yu-Long; Luo, Rui-Ming; Ji, Chen; Gao, Shuang; Bai, Shuang; Wang, Yong-Rui; Dong, Fu-Jia; Hu, Xiao-Lei; Guo, Jia-Jun (Frontiers in Nutrition, 2022)
Taking the eutectic point as the final freezing temperature, the differences of flavor substances of in hand grab mutton (HGM) frozen at three rates of 0. 26 cm/h (−18°C), 0.56 cm/h (−40°C) and 2.00 cm/h (−80°C) were determined and analyzed. The results showed that the flavor of HGM decreased significantly after freezing. With the increase of freezing rate, the contents of aldehydes, alcohols, ketones, acids, esters, others, free amino acids and 5′-nucleotides were higher, and the content of specific substances was also generally increased. All samples from unfrozen and frozen HGM could be divided into four groups using an electronic nose based on different flavor characteristics. Seven common key aroma components were determined by relative odor activity value (ROAV), including hexanal, heptanal, octanal, nonanal, (E)-oct-2-enal, (2E,4E)-deca-2,4-dienal and oct-1-en-3-ol. The higher the freezing rate, the greater the ROAVs. Taste activity values calculated by all taste substances were far <1, and the direct contribution of the substances to the taste of HGM was not significant. The equivalent umami concentration of HGM frozen at −80°C was the highest. These findings indicated that higher freezing rate was more conducive to the retention of flavor substances in HGM, and the flavor fidelity effect of freezing at −80°C was particularly remarkable.